(Engaging or Avoiding) Change Through Reflexive Practices. (April 2019) - Hibbert, Paul; Callagher, Lisa; Siedlok, Frank; Windahl, Charlotta; Kim, Hee Sun
In this article, we explore the ways in which individuals deploy reflexive practices in order to avoid or engage with a call to change either oneself or the social context. We begin by developing a categorization of the modes of reflexive practice associated with avoidance or engagement. We go on to develop—through a relationally reflexive research process—three contributions that build on this. First, we build an understanding of what a repertoire of reflexive practices may include, and "what is going on" in such reflexive practices. Second, we explain how reflexive practices can be mobilizing, thereby enabling shifts between avoidance and engagement modes, or fix action within a single mode. Third, we develop an understanding of the ways in which emotions and relationships influence how reflexive practices of either kind are deployed.